Meta Analysis: Patient’s Satisfaction with the Outpatient’s Telemedicine Service - Putri, Farahdilla Aribowo; Tamtomo, Didik; Prasetya, Hanung (Masters Program in Public Health, Universitas Sebelas Maret, Indonesia, 2024)
Background: Telemedicine is a combination of information and communication technology with medical science to provide health services that are not limited to space and can be done remotely (PB IDI, 2020). Patient satisfaction is referred to as the most integral element in the successful implementation of telemedicine (Ploog et al, 2022). This study aims to compare the satisfaction level of outpatients between telemedicine visits and regular face-to-face visits using meta-analysis. Subjects and Method: This study used a systematic review and meta-analysis based on pico as follows, population: outpatient polyclinic, intervention: telemedicine services, comparison: standard care, outcome: patient satisfaction. Data were obtained from the PubMed, Google Scholar, Springerlink, National Center for Biotechnology Information, MEDLINE, Cochrane Library, and Science Direct databases published from 2020 – 2022. The keywords used in the article search were “telemedicine”, “telehealth”, “ virtual care”, “online follow up care”, “telemedicine vs in office” “telemedicine vs conventional”, “patient satisfaction”, “patient experience”, and “randomized clinical trial.” The inclusion criteria were in the form of a full paper article using a randomized clinical trial design, the subjects were outpatients, new patients and follow-up patients, had a control group that assessed standard services, the study outcomes used the mean SD. Article selection used the PRISMA flowchart and the results were analyzed using Review Manager 5.3 software. Results: A meta-analysis of 10 articles from Hong Kong, Turkey, Germany, Austria, the Netherlands, Ireland and the United States with a sample size of 1412 outpatient polyclinics showed that outpatient polypatients who received telemedicine services had an average satisfaction level of 0.38 points. higher than standard service (SMD= 0.38; 95% CI= -0.01 to 0.77; p= 0.060). The meta-analysis of this study showed significant heterogeneity of effect estimates between studies (I² = 69%; p<0.001), so the analysis used was the Random Effect Model (REM). Conclusion: Patients who received telemedicine services experienced an average satisfaction level of 0.38 higher than patients who received standard services (SMD= 0.38; 95% CI= -0.01 to 0.77; p= 0.060). Keywords: Telemedicine, Patient satisfaction, Meta-analysis Correspondence: Farahdilla Aribowo Putri. Masters Program in Public Health, Sekolah Pascasarjana, Universitas Sebelas Maret. Jl Ir Sutami No. 36A Jebres Surakarta. Email: farahdilla.a.putri@gmail.com. Handphone: +6281333287647.